(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2021)
Bangladesh is regarded as a success story for rapid economic development and changes in social indicators that have taken place in the last couple of decades. Enrolment in education, especially women’s education, has reached a desirable level. However, the dropout rate in secondary education is still a concern, which has not been reduced to the desired level. This research aims to understand better the undisclosed causes of dropout at secondary level schools. The primary data were collected from 790 former secondary school level students and 1580 parents/guardians, enabling in-depth and systematic analysis of the issue.. The method used in this study is quantitative with logit analysis. The study results showed that students’ perceptions on education, working experience, low socio-demographic status (SDS), family size, total number of siblings, food deficit, distance of the school, bullied by peers/teachers have a significant effect on increasing the probability of dropping out of school. Contrariwise, parents’ academic support, NGO membership of family members, mobility to the local power structure, and government’s social safety net programmes support are significant variables to reduce the probability of dropping out. The research reveals that financial problems are severely engaged to increase the dropout rate, and non-financial factors together aggressively play a catastrophic role and lead the academic life of the dropout student towards the end. The study suggests authorities for rapid response to reduce dropout, which leads Bangladesh to achieve SDGs targets and eventually become an upper middle-income country by 2041. J. Asiat. Soc. Bangladesh, Sci. 47(2): 173-190, December 2021